Rain - Stojic, Manya (New York : Dragonfly Books, 2009)
The animals of the African savanna use their senses to predict and then enjoy the rain.
"Published in the United Kingdom by David Bennett Books Limited"--P. facing t.p.
Book Links (A.L.A.)
School Library Journal starred
Wilson's Children
1.7
K-3.
Keywords: Animals -- Juvenile fiction; Rain and rainfall -- Juvenile fiction; Senses and sensation -- Juvenile fiction; Zoology -- Africa -- Juvenile fiction; Animals -- Fiction; Rain and rainfall -- Fiction; Senses and sensation -- Fiction; Zoology -- Africa -- Fiction; Animals -- Africa -- Fiction; Rain -- Fiction; Senses and sensation -- Fiction; Zoology -- Fiction; Africa -- Juvenile fiction; Africa -- Fiction; Africa -- Fiction